2015
DOI: 10.1111/jog.12815
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone and misoprostol compared with misoprostol alone for induction of labor in intrauterine fetal death: A randomized trial

Abstract: Aim: To assess whether mifepristone and misoprostol are more beneficial than misoprostol alone for the induction of labor in women with intrauterine fetal death. Methods: A randomized double blind placebo-controlled parallel group superiority trial was conducted. One hundred and ten women who had experienced fetal death at or later than 20 weeks of gestation were randomized by computer-generated random number sequence to receive 200 mg of mifepristone or matched placebo tablets orally. Misoprostol was administ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 20 publications
1
20
1
Order By: Relevance
“…No direct evidence related to medical management compared with surgical, expectant, or placebo management was identified. Four trials reported that the analysis was intention‐to‐treat (ITT) analysis . Thus, it was not possible to perform true ITT analyses for all comparisons and outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No direct evidence related to medical management compared with surgical, expectant, or placebo management was identified. Four trials reported that the analysis was intention‐to‐treat (ITT) analysis . Thus, it was not possible to perform true ITT analyses for all comparisons and outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Four trials reported that the analysis was intention-to-treat (ITT) analysis. 18,20,23,24 Thus, it was not possible to perform true ITT analyses for all comparisons and outcomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…El Gharib et al 10 has recorded 90% and 45% success rate in the third and second trimester foetal deaths respectively. Chaudhari P et al 12 have achieved 92.5% and 71.2% success rates in their study which compared use of misoprostol with or without mifepristone respectively. P value being 0.001, which was significant.…”
Section: Discussionmentioning
confidence: 96%